2016
DOI: 10.1108/apjba-06-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Importance of commitment in encouraging employees’ innovative behaviour

Abstract: Purpose – The extremely competitive and globalized business environment directs organizations to rely on human capital to be innovative. Committed employees are needed for organizations to foster innovative behaviors. The purpose of this paper is to examine the relationship between three forms of commitment and employees’ innovative behavior. Design/methodology/approach – Adopted questionnaire from previous studies were distributed among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
78
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 37 publications
6
78
2
9
Order By: Relevance
“…As can be seen, all three components of commitment have straightforward implications for staying with (or leaving) an organization, but beyond that, are conceptually quite different (Allen and Meyer, 1996). Research by Munene and Dul (1989) showed that normative commitment is not derived from education, pay or age, but refers to the feeling of mutual trust that establishes an obligation to stay with the organization (Hakimian et al, 2016). Normative commitment might also develop because of the "psychological contract" between an employee and the organization (Rousseau, 1995).…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 4 more Smart Citations
“…As can be seen, all three components of commitment have straightforward implications for staying with (or leaving) an organization, but beyond that, are conceptually quite different (Allen and Meyer, 1996). Research by Munene and Dul (1989) showed that normative commitment is not derived from education, pay or age, but refers to the feeling of mutual trust that establishes an obligation to stay with the organization (Hakimian et al, 2016). Normative commitment might also develop because of the "psychological contract" between an employee and the organization (Rousseau, 1995).…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Meanwhile the second form commitment which is the continuance commitment shows the need by employees to stay with an organization because the cost of leaving is too great or the remuneration factor (Hakimian et al, 2016). Meyer and Allen (1997) revealed that employees with strong continuance commitment may not necessarily want to contribute to their employed organization.…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 3 more Smart Citations